Accuracy and Precision of Non-invasive Cardiac Output Monitoring Devices in Perioperative Medicine: A Systematic Review and Meta-analysis. Issue 4 (August 2017) - Joosten, A.; Desebbe, O.; Suehiro, K.; Murphy, L. S.; Essiet, M.; Alexander, B.; Fischer, M. O.; Barvais, L.; Van Obbergh, L.; Maucort-Boulch, D.; Cannesson, M.
Abstract : (Abstracted from Br J Anaesth, 118(3):298–310, 2017) The main purpose of this article is to provide a systematic review of all medical literature (37 studies; 1543 patients) comparing cardiac output (CO) measured with a commercially available completely noninvasive CO monitoring device against bolus thermodilution (TD) in various clinical settings such as the intensive care unit, emergency department, and the operating room. In addition, the authors provide a meta-analysis of the data extracted from the systematic review to calculate the precision of these noninvasive CO monitoring devices when used perioperatively by following pooled estimates.